A Financial Conditions Index for Greece - Manning, Jonathan; Shamloo, Maral (Washington, D.C. : International Monetary Fund, 2015)
We construct a Financial Conditions Index (FCI) for Greece as a surveillance tool to quantify the degree of the stress in the financial sector. We use principal component analysis to capture the information content of several financial indicators through a single index. We also construct an alternative FCI by purging the business cycle and monetary policy effects on the input variables, and argue that this alternative index is a better indicator of exogenous financial shocks, and thus could be interpreted as a measure of the efficacy of transmission mechanism. We replicate the index for the euro area (EA) as a whole and show that although the developments in the EA were qualitatively in line with those in Greece, they were quantitatively much milder. Our results confirm that monetary transmission was less effective in Greece compared to the EA as a whole. Finally, we argue that our index can be a potentially useful forecasting tool for credit growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet